Morphological and molecular evidence for a new species of the genus Dicranolasma Sørensen, 1873 (Opiliones: Dicranolasmatidae) from Türkiye - Kurt, Kemal; Kurt, Pinar; Yağmur, Ersen Aydin (Zootaxa, 2025)
Dicranolasma ridvansahini sp. nov. (Opiliones: Dicranolasmatidae) is described from Nif mountain, İzmir, Türkiye on the basis of morphological and molecular characteristics. Detailed descriptions and diagnostic features of the new species, as well as illustration of relevant details are given. The new species was compared with some related species in the genus for morphological differences. Additionally, the 28S rRNA gene region was sequenced, and Bayesian Inference (BI) phylogenetic trees were constructed to clarify the species’ evolutionary relationships.